(untitled) (Eurasian Research Bulletin, 2023)
Artificial lung ventilation (ALV) is absolutely and firmly within the practice of intensive care. Effective treatment of seriously ill patients is possible only if sufficient oxygenation is maintained, which can often only be achieved with adequate ventilation. In intensive care units, 2/3 of patients are maintained on mechanical ventilation, which develop various metabolic changes. This article will consider aspects of changes in the structures of the gastrointestinal tract, which are on long-term maintenance of adequate mechanical ventilation